Biology and Management of Whitehead Broom in Pastures - Brent Sellers; James McWhorter (EDIS)
Whitehead broom, also known as shrubby false buttonweed or southern larraflower, is becoming problematic in south Florida pastures, hayfields, and rights-of-way. This 2-page fact sheet discusses a few options to control this species. Written by Brent Sellers and James McWhorter, and published by the UF Agronomy Department, August 2016.